Civilization : The Six Killer Apps of Western Power - Ferguson, Niall (London Penguin Books, 2012)
In 1412, Europe was a miserable backwater ravaged by plague, bad sanitation and incessant war, while the Orient was home to dazzling civilizations. This book reveals the six 'killer applications' that the Rest lacked: competition, science, property rights, medicine, consumerism and the work ethic.
Include Color Illustrations, Bibliography and Index
Keywords: Civilization, Western -- Civilization, Modern -- East and West